Banana tissue culture: community nurseries for African farmers - Kikulwe, Enoch Mutebi (CGIAR Research Program on Roots, Tubers and Bananas, 2016)
This project was carried out in three countries— Kenya, Uganda, and Burundi—to get disease-free, TC banana plantlets to farmers. Private companies were already producing TC banana plantlets, but there was no channel to distribute them to farmers. The project established community nurseries to receive the in vitro-plantlets, wean them, and harden them (i.e. grow them outside of the flask until the plantlets are big and strong enough to be transplanted to farmers’ fields). Eleven new community nurseries were established in Uganda and Kenya to buy the in-vitro plants, harden them, and sell them to farmers. The most successful community nurseries were the ones near their source of TC plantlets and near their farmer customers. About 1,000 farmers were trained to transplant TC bananas to the field and care for them. Although the banana plants are disease free when removed from the flask, they are not disease resistant, and can become infected. The plantlets need extra care when transplanted (e.g. more water and fertilizer). TC was profitable for farmers who were near an urban market, which allowed them to earn higher prices for their harvested bananas. On the other hand, TC plantlets were not profitable for remote farmers.